Forced degradation studies and structural characterization of related substances of bisoprolol fumarate in finished drug product using LC-UV-MS/MS - Lazarevska-Todevska, Elena; Piponski, Marjan; Stefova, Marina (Serbian Chemical Society, 2022)
Methods for determination of bisoprolol and related substances mostly use UV detection and a phosphate buffer and are not suitable for MS detection. In this study, LC?UV?MS/MS for separation and characterization of bisoprolol related substances was developed, validated and applied for studying the degradation products of bisoprolol when exposed to hydrolytic stress, heat and light. The method uses a C18 column, formic acid in water and acetonitrile as mobile phases, gradient elution and UV and MS detection. Forced degradation revealed that acid hydrolysis produces the most intensive transformation of bisoprolol to its impurity A, along with impurities L and D. Alkaline hydrolysis produced impurities A, L, Q, G and K; oxidative and thermal degradation produced impurities A, L and K, while photodegradation produced impurities A, L, G and K, all characterized by their mass spectral data. The developed method using two detection systems was demonstrated as efficient since mass spectra allowed identification of the related substances of bisoprolol and quantification was possible using absorbance measurements at 270 nm. The obtained results will fill in the lack of data on the fragmentation patterns of bisoprolol and related substances that could be used by researchers and practitioners in research and quality control laboratories.
Keywords: bisoprolol impurities; tablets; forced degradation study; fragmentation pathways